Analysis of Hamstring Flexibility on Injury Risk Volleyball Athletes - Anung Probo Ismoko Anung; Yudha Febrianta; Amri Ikhsanul Amal; RD. Devy Citra Pratiwi; Imami Nughraheni; Danang Endarto Putro (Journal of Sports Medicine and Physiotherapy, 2025)
Background: flexibility is a crucial factor in injury prevention in explosive sports like volleyball. Hamstring tightness or limited flexibility can increase the risk of musculoskeletal injuries in the lower limbs. Objectives: This study aimed to analyze the relationship between hamstring flexibility and injury risk in volleyball athletes from the BVB Banyumas club. Methods: This study used a quasi experimental quantitative method with a one group pretest posttest design. The subjects were 20 active junior volleyball athletes selected through purposive sampling. The research instruments included the Sit and Reach Test to measure hamstring flexibility and the Functional Movement Screen (FMS) to assess injury risk. The intervention, a hamstring stretching exercise program, was implemented for 4 weeks, 3 times per week. Data were analyzed using a t-test with a significance level of 0.05. Results: The results showed a significant increase in hamstring flexibility from 18.75 ± 3.08 cm to 23.85 ± 2.96 cm (p = 0.000) and an increase in FMS scores from 13.45 ± 1.31 to 15.80 ± 1.18 (p = 0.000). In addition, the results of the Pearson correlation test showed a strong negative relationship between hamstring flexibility and injury risk (r = -0.726; p = 0.001), which means that the better an athlete's flexibility, the lower their risk of injury. Conclusion: Regular hamstring stretching exercises can improve flexibility and reduce the risk of injury in volleyball athletes. This research demonstrates the importance of flexibility training in preventive and rehabilitative training programs for athletes.